2014
DOI: 10.1002/dneu.22187
|View full text |Cite
|
Sign up to set email alerts
|

VEGF modulates synaptic activity in the developing spinal cord

Abstract: Although it has been documented that the nervous and the vascular systems share numerous analogies and are closely intermingled during development and pathological processes, interactions between the two systems are still poorly described. In this study, we investigated whether vascular endothelial growth factor (VEGF), which is a key regulator of vascular development, also modulates neuronal developmental processes. We report that VEGF enhances the gamma-aminobutyric acid (GABA)/glycinergic but not glutamater… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 40 publications
0
3
0
Order By: Relevance
“…Differentially expressed miRNAs and proteins in SCA-Exo were associated with the VEGF signaling pathway, VEGF-activated receptor activity, and angiogenesis. VEGF is a modulator of the neuronal activity during synapse formation and plays an important role in the nervous system . Previous studies showed that promoting VEGF expression improves the recovery of motor ability after SCI. , Differentially expressed miRNAs and proteins in SCA-Exo were also enriched for “extracellular matrix structural constituent”, “ECM-receptor interactions”, “regulation of actin cytoskeleton”, and “focal adhesion”.…”
Section: Resultsmentioning
confidence: 94%
“…Differentially expressed miRNAs and proteins in SCA-Exo were associated with the VEGF signaling pathway, VEGF-activated receptor activity, and angiogenesis. VEGF is a modulator of the neuronal activity during synapse formation and plays an important role in the nervous system . Previous studies showed that promoting VEGF expression improves the recovery of motor ability after SCI. , Differentially expressed miRNAs and proteins in SCA-Exo were also enriched for “extracellular matrix structural constituent”, “ECM-receptor interactions”, “regulation of actin cytoskeleton”, and “focal adhesion”.…”
Section: Resultsmentioning
confidence: 94%
“…VEGF modulates the GABA and glutamate neurotransmission systems and suppresses epileptic activity in an experimental model of temporal lobe epilepsy [ 300 ]. Moreover, VEGF enhances GABA synaptic transmission during spinal cord development [ 301 ]. The endogenous-acetylcholine-induced VEGF expression in neurons and astrocytes [ 302 ], the VEGF signaling system is in the rescuing effect of acetylcholine on NMDA-induced long-lasting hippocampal cell damage [ 303 ].…”
Section: Receptorsmentioning
confidence: 99%
“…In the developing vertebrate brain, VEGF modulates axonal outgrowth (Sondell et al, 1999 ) and chemoattraction (Ruiz de Almodovar et al, 2011 ), and enhances dendritogenesis (Licht et al, 2010 ). Additionally, VEGF modulates synaptic activity of GABA in spinal neurons (Guerit et al, 2014 ) and glutamate in cerebellum granule cells (Meissirel et al, 2011 ). In the adult mammalian brain, VEGF can be induced to express in neurons (Hayashi et al, 1997 ; Lennmyr et al, 1998 ; Bao et al, 1999 ) and glial cells (Cobbs et al, 1998 ) in the brain following ischemic/hypoxic injury.…”
Section: Introductionmentioning
confidence: 99%